ANALISIS DAMPAK WISATA WATERFRONT TERHADAP PENDAPATAN MASYARAKAT (STUDI KASUS MASYARAKAT TEPIAN KAPUAS KELURAHAN BENUA MELAYU LAUT KECAMATAN PONTIANAK SELATAN) - Yahya, Reski; Syahrudin, Husni; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is a behind the construction of a tourist attraction in the Benua Melayu Laut Village. With the existence of waterfront tourism, it can have an impact on the people of the city of Pontianak, especially the people of the subdistrict of the Melayu Laut sub-district. This study aims to determine the feasibility of tourism based on the concept of Sapta Pesona and how the impact of the construction of waterfront tourism on the income of the people of the sub-district of the continent of Malay sea. This study uses a qualitative method. Data collected through observation, interviews and documentation. The results of the study show that the application of Sapta Pesona in waterfront tourism in its seven elements can be carried out properly but still not entirely optimal, especially in the elements of cleanliness and order. Furthermore, the results related to the impact of waterfront tourism development on people's income with the result that there was a significant increase in income for people who traded at waterfront tourist sites. The average income of the community before selling at tourist sites is Rp. 2,300,000/month, an increase when selling on the waterfront is Rp. 4,000,000/month. From these results, the increase in the difference in income before and after selling on waterfront tourism is Rp. 1700,000/month.